2005
DOI: 10.1016/j.cellbi.2005.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to caspase activation

Abstract: Apoptosis or programmed cell death is an active form of cell death which is essential for tissue homeostasis. Many proteins are involved in the molecular signal transduction of apoptosis. The caspase enzymes, a family of specific cysteine proteases, play a central role in cell death machinery. In this review, we mainly discuss the current understanding of several pathways to activate caspases and some key proteins related to these pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
128
0
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(143 citation statements)
references
References 97 publications
6
128
0
9
Order By: Relevance
“…Ultimately it leads to the activation of caspase-9. Cleaved or active form of caspase-9 cleaves effector caspases including caspase-3, -6, and also -7 (Wang et al 2005). The current study demonstrated that DAM and NDAM-treated H400 OSCC cells exhibited an increase in the activity of Cytochrome c, caspase-9 and also caspase-3/7.…”
Section: Discussionsupporting
confidence: 58%
“…Ultimately it leads to the activation of caspase-9. Cleaved or active form of caspase-9 cleaves effector caspases including caspase-3, -6, and also -7 (Wang et al 2005). The current study demonstrated that DAM and NDAM-treated H400 OSCC cells exhibited an increase in the activity of Cytochrome c, caspase-9 and also caspase-3/7.…”
Section: Discussionsupporting
confidence: 58%
“…1) [22]. The extrinsic apoptotic signaling is initiated by death receptors located on the cell surface, such as the tumor necrosis factor receptor (TNF-R) and the Fas receptor [24]. Activation of these receptors by binding of death-stimulating ligands results in the recruitment of adaptor proteins, such as Fas-associated death domain (FADD), TNF-receptor-associated death domain (TRADD), and TNF-receptor-associated factors (TRAFs), forming the death-inducing signaling complex (DISC), which engages and activates procaspase-8.…”
Section: Signaling Pathways Of Apoptotic Cell Deathmentioning
confidence: 99%
“…Activation of these receptors by binding of death-stimulating ligands results in the recruitment of adaptor proteins, such as Fas-associated death domain (FADD), TNF-receptor-associated death domain (TRADD), and TNF-receptor-associated factors (TRAFs), forming the death-inducing signaling complex (DISC), which engages and activates procaspase-8. Active caspase-8 subsequently activates caspase-3 [24]. Intrinsic pathways of caspase activation include those triggered by the endoplasmic reticulum (ER) and the mitochondrion [22].…”
Section: Signaling Pathways Of Apoptotic Cell Deathmentioning
confidence: 99%
“…Morphological changes in the nucleus include condensation/margination of chromatin, DNA fragmentation in a laddering pattern, and nuclear fragmentation. Apoptotic cells are also characterized by the externalization of phosphatidyl-serine (PS), cell shrinkage, membrane blebbing, a peculiar boiling action of the plasma membrane (zeiosis), and fragmentation of the cell into apoptotic bodies (Vermeulen et al, 2005;Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%